Investigation of the Multicultural Perception Levels of Pre-service Physical Education Teachers: The Case of Western Black Sea - Dogan, Isa (Asian Journal of Education and Training, 2020)
The aim of the current study is to examine the multicultural perception levels of pre-service physical education teachers. In the scope of the study, it was also examined whether the pre-service teachers’ multicultural perception levels differ according to their university, gender, family income level, grade level and general academic achievement grade point average. In this direction, the universities in the Western Black Sea Region were selected and 407 pre-service teachers were interviewed. In the study, which was conducted in a screening design, one of the quantitative research methods, the data were collected with Multicultural Perception Scale developed by Ayaz (2016). The data of the research were analyzed with descriptive statistics, t test for unrelated measurements and Kruskal Wallis test. As a result of the study, it was determined that pre-service teachers’ perceptions of multiculturalism were high. While It was determined that pre-service teachers’ perceptions of multiculturalism did not show a significant change according to their gender and grade levels, there were significant differences according to the university, general academic achievement grade point average and the income level of their families.